Decomposition of four Leucaena and Senna prunings in alley cropping systems under subhumid tropical conditions: the process and its modifiers - Vanlauwe, Bernard; Sanginga, N.; Merckx, Roel (Elsevier, 1997)
A litterbag experiment with Leucaena leucocephala and Senna siamea residues collected during four different pruning activities was carried out in no-tree-control and alley cropping plots. Decomposition was followed for 112 days after the respective pruning dates. Other factors studied were “amount of residue” confined in the litterbags and “plot management” (cropped or bare plots). The leaf litter of the same species, collected during the different prunings had different qualities. Older Leucaena and Senna residues had a lower N content. Older Leucaena residues contained substantially more polyphenols than residues younger than 8 weeks, while 8-week-old Senna residues contained more soluble polyphenols than residues of 29 weeks. The lignin content of the Leucaena residues was greatest for the oldest prunings; while for the Senna residues no clear trend was observed. The decomposition and N release patterns of the four Leucaena and Senna pruning residues were different. The first and second prunings decomposed following first order kinetics. For the third pruning, a negative exponential regression procedure against the number of days where rainfall exceeded pan evaporation (“rainy days”) yielded a better fit than against time. Less than 10% of the dry matter of the fourth pruning decomposed after 112 days. Significant correlations were found between the decomposition rate calculated against the number of “rainy days” and the N content, the C-to-N ratio and the (lignin + polyphenol)-to-N ratio. The N release rate, calculated against the number of “rainy days” correlated significantly with the polyphenol-to-N and (lignin + polyphenol)-to-N ratios. The presence of a fully established crop increased the decomposition and N release of the residues of the second pruning in the no-tree-control plots. The amount of residues confined in the litterbags and the presence of a tree canopy had little effect on residue decomposition.